Normalization of deviance in pediatric hospital: perception of health workers - Gabrielle da Silva Carvalho; Eveline Pinheiro Beserra; Erika da Silva Bandeira; Ana Barbosa Rodrigues; Isaque Lima de Farias; Paloma Moreira de Oliveira; Roberta Meneses Oliveira (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To know the perception of health workers about the phenomenon of normalization of deviance in a pediatric hospital. Method: Exploratory, descriptive, and qualitative study conducted in a public pediatric hospital in northeastern Brazil in 2021. An in-depth interview was applied to 21 health workers, submitted to Thematic Categorical Content Analysis in the MAXQDA® Software. Results: 128 context units emerged from the content analysis. These data were presented in three analytical categories, which address conceptions about normalization of deviance, examples and contributing factors. The omission of the practice of hand hygiene and the correct use of personal protective equipment,and turning off alarms stand out as the main deviance perceived by health workers. As contributing factors, human factors and organizational factors prevailed. Conclusion: Workers perceive the normalization of deviance as negligence, recklessness, and violations of good practices, with consequences for patient safety.